Brain metastases in metastatic cancer: a review of recent advances in systemic therapies. Issue 3 (4th March 2021) - Steindl, Ariane; Berghoff, Anna S.
ABSTRACT: Introduction : Brain metastases (BM) are a frequent complication of metastatic cancer. Due to the wider availability and application of screening procedures, an increasing fraction of patients are diagnosed at the asymptomatic stage. The introduction of immune checkpoint inhibitors and targeted therapies has revolutionized treatment in several frequently BM-causing entities like metastatic lung cancer, melanoma and breast cancer. However, registered trials of new targeted and immunotherapy mostly excluded patients with BM resulting in limited knowledge of the intracranial efficacy of new systemic agents. Areas covered : The present review highlights recent advances in systemic therapies for the treatment and prophylaxis of the three leading BM causing tumors: NSCLC, melanoma and breast cancer. Expert opinion : High intracranial efficacy was observed for several next-generation tyrosine kinase inhibitors as well as immune checkpoint inhibitors, especially in patients with asymptomatic disease. Ongoing discussions addressed the need for local therapies in patients with asymptomatic BM and the availability of systemic therapy with high intracranial efficacy. Further BM-specific studies as well as BM-specific endpoints in registered trials are needed to define the role of systemic monotherapies in patients with BM.